The influence of special motor activity on the formation of individual physical culture of students values - Marchenko A.U (Kharkov National Pedagogical University, 2010)
Influence of the specially organized motive activity is considered on forming values of individual physical culture of students. 70 students took part in an experiment. Employments were conducted during a school year in a volume 4 hours in a week. Indexes which characterize the physical culture of man are presented. Directions of increase motivation to spiritual and physical self-perfection of students are certain. The level of influence of employments is set on a structure and hierarchy of the valued orientations of students.